Quality of life with talazoparib versus physician's choice of chemotherapy in patients with advanced breast cancer and germline BRCA1/2 mutation: patient-reported outcomes from the EMBRACA phase III trial. (15th August 2018) - Ettl, J; Quek, R G W; Lee, K -H; Rugo, H S; Hurvitz, S; Gonçalves, A; Fehrenbacher, L; Yerushalmi, R; Mina, L A; Martin, M; Roché, H; Im, Y -H; et al.
Abstract: Background: In the EMBRACA phase III trial, talazoparib (1 mg daily, orally) demonstrated a statistically significant improvement in PFS versus physician's choice of chemotherapy (PCT; capecitabine, eribulin, gemcitabine, or vinorelbine) in patients with HER2-negative advanced breast cancer carrying a germline BRCA1/2 mutation; we evaluated patient-reported outcomes (PROs). Patients and methods: Patients were randomized 2 : 1 to receive talazoparib or PCT. PROs were assessed at day 1 (baseline), the start of each treatment cycle (every 3 weeks), and at the end of treatment, using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-30) and its breast cancer module, QLQ-BR23. Prespecified exploratory analyses included a longitudinal mixed-effect model comparing treatment arms and a time to definitive clinically meaningful deterioration (TTD) analysis carried out in the global health status/quality of life (GHS/QoL), and all functional and symptom scales from the EORTC QLQ-C30 and -BR23 questionnaires. Between-arm TTD comparisons were made using a stratified log-rank test and a Cox proportional hazards model. Results: Baseline scores were similar between arms. Statistically significant estimated overall improvement from baseline in GHS/QoL was seen for talazoparib compared with statistically significant deterioration for PCT {3.0 [95% confidence interval (CI) 1.2, 4.8] versus −5.4 [95% CI −8.8, −2.0]; between arms, P  <   0.0001}. A statistically significant greater delay was observed in TTD in GHS/QoL, favoring talazoparib over PCT [hazard ratio, 0.38 (95% CI 0.26, 0.55; median, 24.3 versus 6.3 months, respectively; P  <   0.0001)]. A statistically significant overall change and a statistically significant delay in TTD, all favoring talazoparib, were also observed in multiple functions and symptoms. Conclusion: Patients who received talazoparib had significant overall improvements and significant delay in TTD in multiple cancer-related and breast cancer-specific symptoms, functions, and GHS/QoL. ClinicalTrials.gov: NCT01945775.